Meat Consumption outside the Household and Risk Factors for Salmonella Contamination in Meat Based Dishes in Kigali, Rwanda - Niyonzima, Eugène; Ongol, Martin Patrick; Kimonyo, Anasthase; Sindic, Marianne (Gembloux Agro-Bio Tech, 2013)
Meat is world widely known to be a nutrient rich food. It provides valuable amounts of proteins, vitamins such as retinol and vitamin B12 and minerals namely iron, selenium and zinc with an increased bioavailability than found in other dietary sources [1]. Along the production chain, meat can get contaminated by a wide range of spoilage and/or pathogenic microorganisms. Salmonella is reported to be the causal agent of 33 % of food borne outbreaks of bacterial origin attributable to meat [2]. Previous studies have indicated a Salmonella prevalence of 3.4% in meat based dishes consumed within the households of Kigali. However, the consumption pattern as well as the prevalence of Salmonella in meat based dishes consumed outside the household is still unknown. The objective of this study was to determine the meat consumption pattern outside the household’s level and to assess the bacteriological quality of the consumed meat based dishes.